2021
DOI: 10.15587/1729-4061.2021.229184
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the main parameters of the support-lump-breaking coil

Abstract: Agricultural land plays an important role in ensuring food security and employment in rural areas. For many years, the planned economy has forced Uzbekistan to grow water-intensive crops, which has led to declining land productivity and increased crop yields. In a market economy, new innovative technologies are in high demand not only in agriculture but also in other sectors. In order to solve the above-mentioned problems, our research has found it necessary to set goals and objectives. The purpose of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…Only the Fergana Valley shows an excess of the average indicators (for nine indicators), the rest of the regions lag significantly behind. This, to some extent, confirms the leading role of the Fergana Valley in the development of digital technologies in the entire macro region [15].…”
Section: Resultssupporting
confidence: 68%
“…Only the Fergana Valley shows an excess of the average indicators (for nine indicators), the rest of the regions lag significantly behind. This, to some extent, confirms the leading role of the Fergana Valley in the development of digital technologies in the entire macro region [15].…”
Section: Resultssupporting
confidence: 68%
“…Use of highly specialized technologies. This is due to certain features of the storage and processing of products grown in this way [9];  High level of material consumption. The organization of a technical economy requires material costs.…”
Section: Resultsmentioning
confidence: 99%
“…A short review of modern vegetable growing technologies has shown that thanks to new electrotechnological approaches adapted to local conditions, the productivity and sustainability of greenhouse systems is significantly increased. The direction of growing plants in protected ground has a great potential for growth, given the economic growth and high technological level, which makes it possible to obtain high-quality agricultural products [14].…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%